2018
DOI: 10.1002/prca.201800052
|View full text |Cite
|
Sign up to set email alerts
|

Microproteomic Profiling of High‐Grade Squamous Intraepithelial Lesion of the Cervix: Insight into Biological Mechanisms of Dysplasia and New Potential Diagnostic Markers

Abstract: This microproteomic investigation of HSIL gives insights into the biology of cervical precancerous lesions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
24
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

5
0

Authors

Journals

citations
Cited by 15 publications
(26 citation statements)
references
References 64 publications
2
24
0
Order By: Relevance
“…Regardless of the study design, there is consensus concerning the significantly higher specificity and positive predictive value of p16/Ki‐67 immunocytochemistry in tissue specimen compared to cytology or human papilloma virus DNA test results . In the present preliminary investigation, we detected areas of intraepithelial neoplasia by MALDI imaging which may be a starting point for the mass spectrometric diagnosis of cervical intraepithelial neoplasia in squamous and glandular epithelium …”
Section: Discussionmentioning
confidence: 77%
“…Regardless of the study design, there is consensus concerning the significantly higher specificity and positive predictive value of p16/Ki‐67 immunocytochemistry in tissue specimen compared to cytology or human papilloma virus DNA test results . In the present preliminary investigation, we detected areas of intraepithelial neoplasia by MALDI imaging which may be a starting point for the mass spectrometric diagnosis of cervical intraepithelial neoplasia in squamous and glandular epithelium …”
Section: Discussionmentioning
confidence: 77%
“…In a recent investigation, cervical normal squamous (ectocervix), columnar (endocervix) epithelium, and cervical high‐grade squamous intraepithelial lesion (HSIL) were compared by LC‐MS/MS. HSIL are precancerous lesions leading to squamous cell carcinoma (SqCC) of the uterine cervix . Without treatment, it has been estimated that 30–50% of HSIL evolve to SqCC of the cervix .…”
Section: Correlation Of M/z Values Found By Maldi Imaging With Massesmentioning
confidence: 99%
“…LC‐MS/MS‐based shotgun proteomics of tissue can now be performed at a very small scale. Microproteomics allowed us to depict the landscape of proteins associated with high‐grade squamous intraepithelial lesions (HSIL) of the uterine cervix . Such protein maps improve our understanding of the biological background of cervical dysplasia and may contribute to finding new diagnostic or therapeutic targets.…”
mentioning
confidence: 99%
“…In this specific study, we found a nuclear marker—the histone chaperone ASF1B—allowing for the distinction between normal ectocervical epithelium and low‐ and high‐grade dysplastic lesions of the ectocervix. This distinction is highly relevant in pathological diagnostics, since low‐ and high‐grade lesions have different prognosis and lead to different patient monitoring …”
mentioning
confidence: 99%
See 1 more Smart Citation